Raça, mídia e juventude : representações da juventude negra - Nascimento, João Gabriel do (2014)
Commercials conveyed by Veja magazine and television channel Globo in the period of 2001-2010 are the purpose of this historical research, which aims to reflect about the various readings concerning the concepts of race and youth, to identify which representations of black youth are produced, reproduced and disseminated through these advertisements, as well as how these act in social imaginary and influence the identity (des) and (re) constructions of black youth. Based on the answers that the analyzes achieve from the inquired questions, I hope to contribute to the historiographical debate on the topic in focus and a better understanding about the representations of black youth in the advertising industry and the Brazilian social imaginary.